ANALYTE SENSORS WITH METAL-CONTAINING REDOX MEDIATORS AND METHODS OF USING THE SAME (2022)
The present disclosure provides redox mediators having two tridentate ligands and analyte sensors comprising such redox mediators. The present disclosure further provides methods of using such analyte sensors for detecting one or more analytes present in a biological sample of a subject.